2020
DOI: 10.1111/cas.14349
|View full text |Cite
|
Sign up to set email alerts
|

CD4/CD8 ratio is a prognostic factor in IgG nonresponders among peptide vaccine‐treated ovarian cancer patients

Abstract: The identification of useful biomarkers is an urgent issue in cancer treatment, particularly for immunotherapy, as only some patients experience benefits from this treatment. The early induction of the IgG response has been reported as a useful biomarker of favorable prognosis for cancer patients treated with a personalized peptide vaccination, but a portion of these patients (IgG nonresponders) fail to achieve an early induction of IgG response yet experience long‐term survival. It is thus necessary to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The second list of proteins, for which significant specific changes were observed both in the G3 vs. G1 and G3 vs. G2 groups, provides additional insights into the role of several proteins of interest involved in immune functions. The decrease in CD4, associated with a tendency towards an increase in CD8, led to a dramatic decrease in the CD4 to CD8 ratio, a result consistent with previous work demonstrating it represented a favorable prognosis marker for overall survival in vaccine-treated ovarian cancer patients [ 68 ]. Patients with gastric cancer and a low CD4 to CD8 ratio also exhibited 3.6-times higher overall survival compared with patients with a high ratio [ 69 ].…”
Section: Discussionsupporting
confidence: 88%
“…The second list of proteins, for which significant specific changes were observed both in the G3 vs. G1 and G3 vs. G2 groups, provides additional insights into the role of several proteins of interest involved in immune functions. The decrease in CD4, associated with a tendency towards an increase in CD8, led to a dramatic decrease in the CD4 to CD8 ratio, a result consistent with previous work demonstrating it represented a favorable prognosis marker for overall survival in vaccine-treated ovarian cancer patients [ 68 ]. Patients with gastric cancer and a low CD4 to CD8 ratio also exhibited 3.6-times higher overall survival compared with patients with a high ratio [ 69 ].…”
Section: Discussionsupporting
confidence: 88%
“…PCR technology was used for detection of DNA or RNA source biomarkers [17,33,[40][41][42]46,47,49,53,54,57]. The 41 novel prognostic biomarkers provided by 43 studies can be classified by biological function, including cell proliferation and invasion [16][17][18][19][20][21][22], inflammatory response [23][24][25][26][27][28][29], angiogenesis [30][31][32][33], antioxidant [34], immune response [35][36][37][38][39], chemotherapeutic sensitivity [40][41][42][43][44], mitosis process [45], EMT (epithelial-to-mesenchymal transformation) and metastasis [46,47], deregulation of the cellular transport [48] and apoptosis process [31]. The following are representative novel prognostic factors reported in the literature.…”
Section: Blood-based Prognostic Biomarkersmentioning
confidence: 99%
“…[ 36 ] First, the ratio of CD4 and CD8 T cells that express CD69, an early activation marker, is a reliable indicator for clinical efficacy of cancer immunotherapy—lower CD4/CD8 ratio correlates with better treatment outcome. [ 37–39 ] Here, we found that nanovaccine‐treated mice had significantly lower CD4/CD8 ratio than mice treated with free OVA or negative control (Figure 7B), demonstrating that the nanovaccine is more capable of activating CD8‐mediated T cell immunity and may be more effective against tumors. The particle size of the nanovaccine had no impact on the CD4/CD8 ratio.…”
Section: Resultsmentioning
confidence: 83%